Evaluation of Orange-Fleshed Sweet Potato (OFSP) Genotypes for Yield, Dry Matter, Starch and Beta-Carotene Content in Uyo, Southeastern Nigeria - Harry, Gamaliel I.; I. Ulasi, Joseph (International Journal of Environment, Agriculture and Biotechnology, 2022)
Six orange-fleshed sweetpotato genotypes, namely, Naspot-12, Umuspo-1, Lourdes, Erica, Delvia and umuspo-3, sourced from National Root Crops Research Institute, Umudike were evaluated for fresh storage root yield, dry matter, starch and Beta-carotene content in 2020 and 2021 cropping seasons at the Teaching and Research Farm of the University of Uyo. The experiment was laid in a randomized complete block design with three replications. Analysis of variance, correlation and principal component analysis were performed for yield and yield related traits while standard procedure was followed to determine dry matter, starch and beta-carotene content. In this study, results from the analysis of variance showed that the six orange-fleshed sweetpotato genotypes differed significantly (P≤ 0.05) in number of marketable roots, weight of marketable roots and fresh storage roots yield. Umuspo-3 produced the highest storage root yield (28.78t/ha, 27.55t/ha) in 2020 and 2021 cropping seasons, respectively. The result of the correlation analysis also revealed that number of marketable roots and weight of marketable were highly significantly and positively (P< 0.01) correlated with fresh root yield. Principal component analysis (PCA) had two main principal components explaining 70.25% of the total variation with number of marketable roots, weight of marketable tuber and storage root yield contributing the most to the first PCA. Umuspo-3 recorded the highest dry matter content of 42.78%. Lourdes had the highest starch content, 65.23mg100g-1 while Umuspo-3 had the lowest starch content, 24.55mg100-1. Beta-carotene content of the six OFSP genotypes ranged from 1.03mg/100g FW to 9.19mg/100g FW. Umuspo-3 recorded a Beta-carotene content of 9.19 mg/100g FW.Umuspo-3 genotype could be recommended for cultivation in Uyo agro-ecology for high yield and as an excellent source of beta-carotene, it could be consumed to ameliorate vitamin A deficiency in children and pregnancy women within the State and its environs.